Analytical psychology and habitation: Interfaces between psyche and housing - Daré, Paula Serafim (Revista ARA, 2021)
Jung's work interacts with several areas of knowledge: religion, alchemy, art, and cultural history. This work aims to establish a relationship between physical housing and psychological characteristics from individual, social, and cultural points of view and their relationship with neuroscience.